A Comparison Between the Relaxation/Meditation/Mindfulness Tracker t Inventory and the Freiburg Mindfulness Inventory for Predicting General Health, Anxiety, and Anger in Adult General Population - Malakoutikhah, Alireza; Zakeri, Mohammad Ali; Dehghan, Mahlagha (Frontiers in Psychology, 2022)
Introduction An individual’s level of mindfulness can predict his/her level of general health, anxiety, and anger. If we have a valuable tool for measuring mindfulness, we can predict such factors more concisely. Therefore, the aim of this study was to compare a narrowband and a broadband mindfulness scale in predicting the level of general health, anxiety, and anger in a general population. Materials and Methods This was a cross-sectional study on an Iranian general population (all citizens living in Kerman) from September 22, 2020 to April 14, 2021. The convenience sampling method was used. Data were collated via electronic and paper forms of the Relaxation/Meditation/Mindfulness Tracker t-Persian version (RMMt-P), the Freiburg Mindfulness Inventory- Short-Form-Persian version (FMI-P), the General Health Questionnaire, the trait anxiety section of the State–Trait Anxiety Inventory, and the trait anger section of the State–Trait Anger Expression Inventory-2. Results The FMI-P predicted 0.05% of GHQ variance while the first and third levels of RMMt-P predicted 0.145%. The FMI-P predicted 0.19% of anxiety variance, while the first and third levels of RMMt-P predicted 0.195%. The FMI-P predicted 0.0% of anger variance, while the first, second, and third levels of RMMt-P predicted 0.08%. RMMt-P Level 1 was a better predictor of general health, anger, and anxiety. Conclusion The current study found that the RMMt-P was a better predictor of general health and anger than the FMI-P. These findings suggest that the type of questionnaire used in the study of mindfulness is important, but more research is needed to determine the extent of these relationships.